EFISIENSI PENGGUNAAN MODAL, TENAGA KERJA, DAN LUAS LAHAN TERHADAP PRODUKSI SALAK DI KECAMATAN BEBANDEM KABUPATEN KARANGASEM - Ragita, Karmila Putri; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 4 (2022): Vol. 11 No. 4, April 2022 [1215-1619]DO - 10.24843/EEP.2022.v11.i04.p12, 2022)
The agricultural sector is a very important sector, efficiency in the use of capital, labor and land area is an absolute thing for a farmer, this is because agricultural businesses require a lot of financing. The purpose of this study was to determine the effect of capital, labor, and land area on production and to determine the level of efficiency and the resulting scale of production. Data used primary data, with sample used 90 respondents. The sampling technique used is non-saturated sampling. Using multiple linear regression analysis techniques. The results of this study indicate that capital, labor, and land area have a simultaneous effect on production. Capital has a partially significant effect on production, labor has a partially significant effect on production, and land area has a partially significant effect on production. The efficiency level of capital and labor is already efficient and its use can still be increased and the land area is not efficient so there is no need to increase its use. The scale of production is in increasing return to scale. The most influential variable on production is land area. Keywords : capital efficiency, labor, land area, productivity